Perencanaan Service Level Management Layanan TI pada PPTI Stikom Surabaya menggunakan ITIL V3 - Addaba, Abdullah; Sutomo, Erwin; Slamet, Slamet (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PPTI is part that serves as a supporter of business process and responsible develop and apply and communication in stikom surabaya that can develop corporate governance effective, efficient and productive in operational ppti do not have jaminan-jaminan as well as the relative warranty each user to service of the most dominant namely stikomapps, sicyca, brilliant, tissue via the cable and wireless. With his planning management service level parties ppti can ( 1 ) determine , document , monitor , measuring and controlling services ti available .( 2 ) provide and increase hubuungan and a communication between service with ti ( 3 sure that the target of the services have specific and measurable so that it can improve their services IT. In this study producing a design framework sla , 5 documents slr to the needs of design sla , 5 documents sla as security users from the healthcare providers , 3 documents ola as a treaty among parts providers and the documents sip as the development services.